2011
DOI: 10.1007/s12272-011-0207-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-allergic activity of sesquiterpenes from the rhizomes of Cyperus rotundus

Abstract: From the 70% ethanol extract of the rhizomes of Cyperus rotundus (CRE), several major constituents including the sesquiterpene derivatives (valencene, nootkatone, and caryophyllene α-oxide), monoterpenes (β-pinene, 1,8-cineole, and limonene) and 4-cymene were isolated and examined for their anti-allergic activity in vitro and in vivo. In rat basophilic leukemia (RBL)-1 cells, the sesquiterpenes strongly inhibited 5-lipoxygenase-catalyzed leukotrienes production. In addition, they inhibited β-hexosaminidase rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 20 publications
2
55
0
1
Order By: Relevance
“…The inhibition was concentration-dependent with an IC 50 value of (32.05 ± 3.91) μg/ml (the positive control NDGA exhibited an IC 50 value of 0.24 μg/ml). This 5-LOX inhibition activity may be attributed to the high content of D-limonene, which exhibits an IC 50 value of 13 μg/ml (Jin et al, 2011).…”
Section: -Lipoxygenase Inhibitionmentioning
confidence: 98%
“…The inhibition was concentration-dependent with an IC 50 value of (32.05 ± 3.91) μg/ml (the positive control NDGA exhibited an IC 50 value of 0.24 μg/ml). This 5-LOX inhibition activity may be attributed to the high content of D-limonene, which exhibits an IC 50 value of 13 μg/ml (Jin et al, 2011).…”
Section: -Lipoxygenase Inhibitionmentioning
confidence: 98%
“…It has also been reported that C. rotundus showed cytotoxic and apoptosis-inducing effects against various tumor cells (Kilani et al, 2008;Kilani-Jaziri et al, 2009;Sayed et al, 2007). Jin et al (2011) reported that sesquiterpenes prepared from a 70% ethanol extract of the rhizomes of C. rotundus exerted significant anti-allergic activity in vitro and in vivo. Nootkatone, a sesquiterpene isolated from C. rotundus, was found to have potent inhibitory effects on collagen-, thrombin-and arachidonic acid-induced platelet aggregation (Seo et al, 2011).…”
Section: Introductionmentioning
confidence: 95%
“…1 Also, they are used as a remedy for renal colic and dysentery. 2 Furthermore, the plant possesses different biological activities such as antioxidant, [3][4][5] cytotoxic, 3,5 anti-allergic, 6,7 antipyretic, anti-inflammatory, antiemetic, hypotensive, 8 anticonvulsant, 9 anti-malarial, antimicrobial, 10,11 anti-diarrhoeal, 12 anti-diabetic, 5,13,14 hepatoprotective, 14,15 and insecticide. 16,17 The previous phytochemical studies of C. rotundus L. led to the isolation of sesquiterpenes, 13,[18][19][20][21][22][23] flavonoids, 3,5,8,24,25 phenylpropanoids, 5,26,27 phenolic acids, 5,26 alkaloids, 28 and saponins.…”
Section: Introductionmentioning
confidence: 99%